2013
DOI: 10.1136/oemed-2013-101717.38
|View full text |Cite
|
Sign up to set email alerts
|

38 Occupational hazards in some selected small scale industries in a district of Sri Lanka

Abstract: Occupational hazards in some selected small scale industries in a district of Sri Lanka Objective To identify occupational hazards in the work environment in small scale industiries in a district of Sri Lanka Method A descriptive cross sectional study was carried out in selected categories of small scale industries namely food and beverages, apparel, non metallic mineral products and fabricated metal products in a district of Sri Lanka. A small scale industry was defined as a work setting with less than 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…In accordance with the present results, a previous study reported that noise was one of the most frequent occupational hazards reported by 78.3% (15). Additionally, 34% of the factories and 27.4% of the participants respectively produced a high level of noise (16,17).…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the present results, a previous study reported that noise was one of the most frequent occupational hazards reported by 78.3% (15). Additionally, 34% of the factories and 27.4% of the participants respectively produced a high level of noise (16,17).…”
Section: Discussionsupporting
confidence: 93%